2016
DOI: 10.22146/jml.18769
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH KONTAMINASI LOGAM BERAT DI SEDIMEN PADA KOMUNITAS MAKROZOOBENTOS DI BEBERAPA SITU DAN WADUK DI JAWA BARAT (Effect of Heavy Metals Contamination in Sediments on The Macrozoobenthos Community in Some Small Lakes and Reservoirs)

Abstract: AbstrakKeberadaan logam berat di ekosistem akuatik telah sering dilaporkan menimbulkan masalah ke biota perairan. Salah satu biota perairan yang memiliki resiko untuk terpapar logam berat dari sedimen adalah organisme makrozoobentos. Penelitian ini bertujuan untuk mendeskripsikan pengaruh kontaminasi logam berat di sedimen pada struktur komunitas makrozoobentos yang berada di ekosistem lentik (situ dan waduk). Penelitian ini telah dilakukan pada bulan Juni 2009 -September 2011 di beberapa situ dan waduk yang b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Lake Cikaret is located in Cibinong, Bogor, Indonesia, which functions as flood control, raw water supply for irrigation and fisheries, recreation, and water absorption area (Sulawesty 1996;Sudarso et al 2016;Sulistianingsih et al 2019;Sulastri et al 1994;Supriyadi et al 2015). The water comes from the Bantenan River and the Kebantenan River, while the water goes out into the Tambakan River and the Cikaret River.…”
Section: Methodsmentioning
confidence: 99%
“…Lake Cikaret is located in Cibinong, Bogor, Indonesia, which functions as flood control, raw water supply for irrigation and fisheries, recreation, and water absorption area (Sulawesty 1996;Sudarso et al 2016;Sulistianingsih et al 2019;Sulastri et al 1994;Supriyadi et al 2015). The water comes from the Bantenan River and the Kebantenan River, while the water goes out into the Tambakan River and the Cikaret River.…”
Section: Methodsmentioning
confidence: 99%
“…The earlier study reported that the DO in Situ Cikaret was below standard in 2010 and 2019, and this may influence the fish condition. Based on Tellar [20], those situ were categorized as moderately polluted with the arsenic concentration above the severe effect level (SEL) of 33 ppm, cadmium and lead level above low effect level (LEL) 0.6 ppm for cadmium and 31 ppm for lead in 2011 [21]. Fish has a lifespan of more than 1.5 years for small fish and might be longer for large fish, so the exposure to heavy metals can occur during their life [22].…”
Section: Table 2 Environmental Parameters In Situ Cikaret and Situ Ci...mentioning
confidence: 99%
“…Currently, macrozoobenthic are beginning to be applied as biological indicators to observe the level of exposure to heavy metals [8], [13], [43]. In this study, Baetidae, Hydropsychidae and Elmidae were selected as indicator organisms to be studied for the concentration of heavy metals in their bodies and then compared with the quality standards set by BPOM Regulation.…”
Section: Heavy Metal Concentrationmentioning
confidence: 99%
“…Heavy metals accumulate a lot in sediments, while the bottom substrate of the waters is a living place for macrozoobenthic, potentially contaminating them with heavy metals. Sudarso, et al [8] report that the presence of heavy metals can eliminate more sensitive species and reduce the diversity and richness of macrozoobenthic. Macrozoobenthic comprises a group of aquatic animals contributing to the ecosystem's stability.…”
Section: Introductionmentioning
confidence: 99%